Development of Digital Al-Qur'ran Application for Vocational School Entrepreneur Tahfidz Genteng Through a Design Thinking Approach - Abdurrochim Abdurrochim (Jurnal Indonesia Sosial Teknologi, 2024)
This research develops a digital Qur'an application centered on the needs of its users in the world of education. The purpose of this study is to find out user needs, design a prototype of the digital Qur'an application, and to find out the newness of the application based on user needs. This research uses the Design Thinking method in each stage, namely the stage of problem analysis (empathize), problem framing (define), determination of ideas and solutions (ideate), product design (prototype), and product testing (test). Based on the response of users in the empathize stage with a sample of 43 people selected by random sampling and then analyzed at the define stage, it was found that users need an application that has good security features, users need learning features related to Islam, users need a feature that can review reading and memorization progress, users need a word-by-word and per-verse translation feature for free, and users need an application that does not take up much space on the phone's memory. Based on the results of the research on the development of the digital Qur'an application, it was found that there are 2 new features of the digital Qur'an application that suit the needs of users. These features are features to review the progress of reading and memorization as well as features that contain Islamic teachings such as the teachings of aqidah, morals, hadith, Do-a collections and shalawat collections.